2021
DOI: 10.1002/rra.3834
|View full text |Cite
|
Sign up to set email alerts
|

Floodplain connectivity and age‐0 sturgeon prey consumption in the lower Missouri River

Abstract: Floodplains are generally considered important nursery habitat for young fish, but little information exists regarding the importance of this habitat for Scaphirhynchus sturgeon. During 2019, the lower Missouri River experienced widespread, prolonged floodplain connectivity, and this study provides the first documentation of age-0

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…One potential explanation for the observed growth is that extensive flooding during 2019 provided increased prey resources in the LMOR. However, Gosch et al (2021) [13] documented that age-0 Scaphirhynchus sturgeon (≤120 mm) captured from floodplain and mainstem habitats in 2019 did not have increased condition (based on length-weight relationships) compared to other years. Additionally, condition declined for many juvenile pallid sturgeon (400 to 699 mm) following the 2011 LMOR flood [14].…”
Section: Discussionmentioning
confidence: 99%
“…One potential explanation for the observed growth is that extensive flooding during 2019 provided increased prey resources in the LMOR. However, Gosch et al (2021) [13] documented that age-0 Scaphirhynchus sturgeon (≤120 mm) captured from floodplain and mainstem habitats in 2019 did not have increased condition (based on length-weight relationships) compared to other years. Additionally, condition declined for many juvenile pallid sturgeon (400 to 699 mm) following the 2011 LMOR flood [14].…”
Section: Discussionmentioning
confidence: 99%
“…Intuitively, one hypothesis explaining these results would implicate the connection with floodplain habitat as a result of increased river discharge. However, Gosch et al (2021) found that age‐0 sturgeon captured in LMOR floodplain habitats during a year of prolonged and extensive flooding did not experience better foraging compared to individuals captured in mainstem habitats during other years, suggesting mechanisms other than floodplain connectivity, such as the timing of high flow events.…”
Section: Discussionmentioning
confidence: 99%
“…A modeling study from a tributary of the LMOR (the Platte River, NE) suggested a potential link between age‐0 shovelnose sturgeon year‐class strength and discharge (Goto et al, 2014), but understanding the role of discharge and other potential variables in the LMOR will require additional research. In general, a lack of food during early life history is likely not a limiting factor for shovelnose sturgeon (Civiello et al, 2018; Gemeinhardt et al, 2019; Gosch et al, 2021), but understanding the conditions leading to year–class strength of age‐0 sturgeon is clearly important to population management. This could also have important implications for endangered pallid sturgeon if shovelnose sturgeon are validated as a diet surrogate for this species during early life history.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation